Current and future plant invasions in protected areas: Does clonality matter?. Issue 12 (7th October 2021) - Wan, Ji‐Zhong; Wang, Chun‐Jing; Zimmermann, Niklaus E.; Li, Mai‐He; Pouteau, Robin; Yu, Fei‐Hai
Abstract: Aim: Protected areas (PAs) play an important role in biodiversity conservation, but remain increasingly threatened by invasive alien plant species (IAPS) in conjunction with global climate change. The latter is modifying the distribution of the former, and the magnitude and direction of distributional changes are predicted to vary depending on species dispersal mode. Here, we address the question of whether clonality is expected to affect the future invasion pattern in PAs. Location: Worldwide. Time period: 1950–2100. Major taxa studied: 36 invasive alien plant species. Methods: We used ensembles of three species distribution models (GLM, GAM and Maxent) based on >70, 000 occurrence records to project the distribution of 36 of the world's most invasive clonal and non‐clonal plants in >20, 000 PAs. Projections were based on three greenhouse gas concentration scenarios (low, medium and high) for 2080. Results: Climate change showed little impact on the global invasion pattern in PAs, and clonality showed little effect when all biomes were processed in concert. However, we discerned that the future invasion risk of clonal IAPS markedly increased in biomes located at high elevation and high latitude compared with non‐clonal IAPS, while the risk decreased in lower‐elevation tropical and subtropical biomes where asexual reproduction may be a less successful trait. We also showed that invasion hot spots overlapped with biodiversity hot spots and two realms (i.e. Nearctic and Palearctic), which calls for bridging the gap between invasion and conservation sciences and for more concerted management strategies. Main conclusions: We suggest that effective management of IAPS in PAs should consider in which biomes PAs are located as well as the reproductive traits of IAPS that are present or may become so.